New species of Ateuchus and Canthidium (Coleoptera: Scarabaeidae: Scarabaeinae) from Costa Rica - Kohlmann, Bert; Solis, Angel (Zootaxa, 2009)
The following new species of dung beetles (Coleoptera: Scarabaeidae) from Costa Rica are described: Ateuchus earthorum sp. nov. (Ateuchini) and Canthidium (Eucanthidium) darwini sp. nov. (Coprini). Illustrations of the dorsal habitus of the new species and a distribution map are provided, as well as a drawing of the internal sac of Ateuchus earthorum sp. nov.